Production‐level risk factors for syncytial hepatitis in farmed tilapia (Oreochromis niloticus L). Issue 1 (17th September 2017) - Kabuusu, R M; Aire, A T; Stroup, D F; Macpherson, C N L; Ferguson, H W
Abstract: Syncytial hepatitis (SHT) is an emerging viral disease of tilapia characterized by significant morbidity and mortality. This study aimed to establish the production‐level risk factors associated with presence and severity of SHT. Production factors were analysed during multiple outbreaks of SHT that occurred between 2011 and 2013 on a single tilapia farm in Ecuador and compared with the year 2010 before the SHT outbreaks. Relative risks, t tests, modified Poisson and forward stepwise linear regression analyses were performed using EPIINFO™. Compared to other strains, Chitralada had an elevated risk of SHT [RR = 2.1 (95%CI 1.8–2.4)]. Excessive mortality associated with the presence (and severity) of SHT increased by 611 (365), 6, 814 (5, 768) and 388 (340) deaths per 100, 000 fry when stocking density, dissolved oxygen and pond production cycles were raised by 1 fish/m 2, 1 mg/L and 1 cycle, respectively. Excessive mortality associated with the presence (and severity) of SHT decreased by 337 (258) and 1, 354 (1, 025) deaths per 100, 000 when stocking weight and water temperature increased by 1 g and 1°C, respectively. Time (season and stocking year) was not significantly associated with SHT. This study shows that some production factors increase the risk incidence and severity of SHTon a farm.